Heart Failure Association of the European Society of Cardiology position paper on the management of left ventricular assist device‐supported patients for the non‐left ventricular assist device specialist healthcare provider: Part 2: at the emergency department. (14th September 2021) - Milicic, Davor; Ben Avraham, Binyamin; Chioncel, Ovidiu; Barac, Yaron D.; Goncalvesova, Eva; Grupper, Avishai; Altenberger, Johann; Frigeiro, Maria; Ristic, Arsen; De Jonge, Nicolaas; Tsui, Steven; Lavee, Jacob; et al.
Abstract: The improvement in left ventricular assist device (LVAD) technology and scarcity of donor hearts have increased dramatically the population of the LVAD‐supported patients and the probability of those patients to present to the emergency department with expected and non‐expected device‐related and patient–device interaction complications. The ageing of the LVAD‐supported patients, mainly those supported with the 'destination therapy' indication, increases the risk for those patients to suffer from other co‐morbidities common in the older population. In this second part of the trilogy on the management of LVAD‐supported patients for the non‐LVAD specialist healthcare provider, definitions and structured approach to the LVAD‐supported patient presenting to the emergency department with bleeding, neurological event, pump thrombosis, chest pain, syncope, and other events are presented. The very challenging issue of declaring death in an LVAD‐supported patient, as the circulation is artificially preserved by the device despite no other signs of life, is also discussed in detail.